2017
DOI: 10.1002/dys.1557
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term Memory in Childhood Dyslexia: Deficient Serial Order in Multiple Modalities

Abstract: In children with dyslexia, deficits in working memory have not been well-specified. We assessed second-grade children with dyslexia, with and without concomitant specific language impairment, and children with typical development. Immediate serial recall of lists of phonological (nonword), lexical (digit), spatial (location), and visual (shape) items were included. For the latter three modalities we used not only standard span but also running span tasks, in which the list length was unpredictable to limit mne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
54
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 61 publications
7
54
0
1
Order By: Relevance
“…A longitudinal study of children with and without dyslexia risk showed that capacity for verbal and nonverbal serial order learning was associated with reading ability and phonological awareness (Bogaerts, Szmalec, De Maeyer, Page, & Duyck, 2016). A deficit in maintaining serial order in short-term memory across several modalities was confirmed in a sample of children with dyslexia with and without concomitant language impairment (Cowan et al, 2017). Several studies showed that serial-order learning, both in the verbal and nonverbal modality, was found to be deficient in adults with dyslexia as well (Bogaerts, Szmalec, Hachmann, Page, & Duyck, 2015; Hachmann et al, 2014; Szmalec, Loncke, Page, & Duyck, 2011).…”
Section: Known Sequential Processing Deficits In Dyslexiamentioning
confidence: 94%
“…A longitudinal study of children with and without dyslexia risk showed that capacity for verbal and nonverbal serial order learning was associated with reading ability and phonological awareness (Bogaerts, Szmalec, De Maeyer, Page, & Duyck, 2016). A deficit in maintaining serial order in short-term memory across several modalities was confirmed in a sample of children with dyslexia with and without concomitant language impairment (Cowan et al, 2017). Several studies showed that serial-order learning, both in the verbal and nonverbal modality, was found to be deficient in adults with dyslexia as well (Bogaerts, Szmalec, Hachmann, Page, & Duyck, 2015; Hachmann et al, 2014; Szmalec, Loncke, Page, & Duyck, 2011).…”
Section: Known Sequential Processing Deficits In Dyslexiamentioning
confidence: 94%
“…General processing speed has been found to reflect in problems of RAN, to predict reading fluency, and to mediate the RAN—reading association among children (Papadopoulos et al, ). Moreover, earlier studies indicate WM problems to be related to reading difficulties and to RAN—reading relationship among children (Cowan et al, ; Majerus & Cowan, ; Papadopoulos et al, ). However, knowledge of how adult‐age processing speed and WM are related to adult‐age reading skills or to persistence of childhood RD is insufficient.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, this common learning disability involves about 80 percent of the learning disabled population, although the prevalence rate may differ from country to country [16]. Many researchers report that dyslexia is created by four causes: perceptual deficits [17][18][19][20][21], memory deficits [22,23], language processing deficits [7], and visual processing deficits [24][25][26]. Dyslexia does not only affect reading and writing but it has also been proved to cause topographic disorders and orientation problems [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%